Neuronal ensembles sufficient for recovery sleep and the sedative actions of alpha(2) adrenergic agonists - Zhang,Z; Ferretti,V; Guentan,I; Moro,A; Steinberg,EA; Ye,Z; Zecharia,AY; Yu,X; Vyssotski,AL; Brickley,SG; Yustos,R; Pillidge,ZE; et al. (Nature Neuroscience, 2015)
Do sedatives engage natural sleep pathways? It is usually assumed that anesthetic-induced sedation and loss of righting reflex (LORR) arise by influencing the same circuitry to lesser or greater extents. For the α2 adrenergic receptor agonist dexmedetomidine, we found that sedation and LORR were in fact distinct states, requiring different brain areas: the preoptic hypothalamic area and locus coeruleus (LC), respectively. Selective knockdown of α2A adrenergic receptors from the LC abolished dexmedetomidine-induced LORR, but not sedation. Instead, we found that dexmedetomidine-induced sedation resembled the deep recovery sleep that follows sleep deprivation. We used TetTag pharmacogenetics in mice to functionally mark neurons activated in the preoptic hypothalamus during dexmedetomidine-induced sedation or recovery sleep. The neuronal ensembles could then be selectively reactivated. In both cases, non-rapid eye movement sleep, with the accompanying drop in body temperature, was recapitulated. Thus, α2 adrenergic receptor–induced sedation and recovery sleep share hypothalamic circuitry sufficient for producing these behavioral states.